2002
DOI: 10.1002/sdr.231
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and managing innovation processes

Abstract: The lecture was delivered at the Prize ceremony during the 19th International Conference of the System Dynamics Society in Atlanta, Georgia. It summarizes the Award winning article, published in the 1996 issue of System Dynamics Review, and discusses subsequent work. Comprehensive citations and quotations are found in the original publications. Shortened product life cycles, tight competition, and resource intensive research and development are some of the parameters that make innovation management a highly ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 8 publications
1
25
0
1
Order By: Relevance
“…This research may inform these discussions in the literature because we propose and test formal methods for linking qualitative system maps and quantitative simulation models. Finally, Warren (2002), Morecroft (1984Morecroft ( , 1985, Morecroft and Sterman (1994) and Milling (2002), among others, have demonstrated that formal system dynamics models can be powerful supports for strategic planning. From a different analytic tradition, scenario analysis ( Van der Heijden, 1996;Wack, 1985) is one of the crucial tools for strategic planning often revealing counter-intuitive effects and dynamic behavior.…”
Section: Three Threads Of Research Which Inform This Workmentioning
confidence: 97%
“…This research may inform these discussions in the literature because we propose and test formal methods for linking qualitative system maps and quantitative simulation models. Finally, Warren (2002), Morecroft (1984Morecroft ( , 1985, Morecroft and Sterman (1994) and Milling (2002), among others, have demonstrated that formal system dynamics models can be powerful supports for strategic planning. From a different analytic tradition, scenario analysis ( Van der Heijden, 1996;Wack, 1985) is one of the crucial tools for strategic planning often revealing counter-intuitive effects and dynamic behavior.…”
Section: Three Threads Of Research Which Inform This Workmentioning
confidence: 97%
“…He terms systems as tightly (antonym: "loosely") coupled, if an accident is spreading quickly throughout the system. Note that the dimensions "complex-linear" and "tightly-loosely coupled" are sometimes addressed by the term "complexity", which has the dimensions of variety, connectivity, and functionality (Milling, 1981(Milling, , 2002. In a system with a high number of elements which are closely connected and where the functionalities of those connections are nonlinear, minor failures can end in severe accidents because such systems are nontrivial and hence unpredictable (Perrow, 1984).…”
Section: Introductionmentioning
confidence: 98%
“…This trend implies a limitation in the econometric case study approach. Other researchers have attempted to model a company's promotional activities [11][12][13][14][15]. The present study aims to illuminate the management of a corporate scandal based on the company's protective activities.…”
Section: Introductionmentioning
confidence: 99%